An overview of vertical farming: highlighting the potential in Malaysian high-rise buildings - Sengodan, Papathy (Universiti Putra Malaysia Press, 2022)
Recently, there has been a surge of interest in sustainable agriculture to address the impact of urban paradigm shifts on food demand and supply. Vertical Farming (VF) has attracted considerable attention, both scholarly and economically, as a way forward to improve food security in urban areas. Previous studies have documented and reviewed the benefits of VF against traditional agriculture. However, most research papers have only focused on case studies from temperate climate regions. There is a surprising paucity of empirical research in urban farming specifically related to VF in tropical countries. This study set out to examine the new emerging agricultural innovation—VF—in various building typologies the growing system and explores the feasibility in Malaysian high-rise buildings. The findings also revealed several successful outcomes of ongoing urban farming projects in Malaysia, Singapore and Thailand, which can significantly contribute to the planning and development of VF in a tropical climate. As a result, critical assessment criteria were identified for the successful development of the VF system in urban areas. This study implies significant opportunities for Malaysia to implement VF in local high-rise buildings.